PENGEMBANGAN MODEL PROBLEM BASED LEARNING (PBL) TERINTEGRASI INKUIRI TERBIMBING PADA PELAJARAN KIMIA LARUTAN DI SMA KELAS XI UNTUK MENINGKATKAN HASIL BELAJAR KIMIA DAN NILAI KARAKTER Dkmtj SISWA - Eka Kartika Silalahi; Ramlan Silaban; Albinus Silalahi (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract   This study aims to analyzed (1) The difference of chemical enhancement of learning outcomes of students who were taught significantly between Instrusction Direct (DI) model, Problem Based Learning (PBL) and guided inquiry, and Problem Based Learning (PBL) and guided inquiry with computers, (2) Differences of character Dkmtj students enhancement as significantly were taught using Instrusction Direct (DI) learning model, Problem Based Learning (PBL) and guided inquiry and Problem Based Learning (PBL) and guided inquiry with computers, and (3) the relationship between the character and chemical students outcomes with the learnin towards learning model is applied. This studied was experimental. The population was all students high school of XI class in Pematangsiantar town as 2013/2014 Academic Year. Sampling technique used cluster random sampling, that was SMAN 2, SMAN 3 and SMAN 4 Pematangsiantar respectively 3 classes. The research instrument was studying chemistry test results and observations increased in the value of the character of students. The data analysis technique used the analysis of variance (ANOVA) 1 way (One way ANOVA) with SPSS 20 for windows at significance level α = 0.05. Based on the results of data processing, it was concluded (1) Significantly there were differences in learning outcomes between students who were taught chemistry learning model of Direct Instruction (DI) compared with the model of Problem Based Learning (PBL) as compared with the integrated guided inquiry model of Problem Based Learning (PBL) is integrated guided inquiry using computer. (2) Significantly there were differences of character values ​​of discipline, critical thinking, independent, responsible and honest that was developed between the students who were taught by the learning model of Direct Instruction (DI) compared with the model of Problem Based Learning (PBL) integrated guided inquiry model than the Problem based Learning (PBL) integrated guided inquiry using the computer. (3) Significantly there is a relationship with the learning outcomes of the character values ​​of discipline, critical thinking, independence, accountability and integrity are spreading among the students who are taught by the model of Problem Based Learning (PBL) and the integrated guided inquiry model of Problem Based Learning PBL integrated guided inquiry using a computer. Keywords: Problem Based Learning (PBL), Guided Inquiry and Direct Instrusction (DI)